2020
DOI: 10.14202/vetworld.2020.188-196
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of alpha-lipoic acid and omega-3 fatty acids against cyclophosphamide-induced ovarian toxicity in rats

Abstract: Background and Aim: Cyclophosphamide therapy is known to be associated with the risk of female infertility as a result of ovarian toxicity. Alpha-lipoic acid (LA) and omega-3 fatty acids are known for their antioxidant and anti-inflammatory activities. The present study investigated the potential protective effect of alpha-LA, omega-3 fatty acids, and its combination against cyclophosphamide-induced ovarian toxicity in rats. Materials and Methods: Thirty rats were equally divided into Groups I, II, II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 61 publications
1
13
0
Order By: Relevance
“…Previous studies have noted that ALA can enhance the antioxidants enzymes like superoxide dismutase, by reducing the substrate and free radicals to promote the lipid stability in birds (Kofuji, Nakamura, Nakamura, Isobe, Murata, & Kawashima, 2008;Li et al, 2019 (Liu, Lin, Mi, Li, et al, 2018;Liu, Lin, Mi, Zeng, et al, 2018). ALA has been reported to increase the reproductive hormones in ovarian oxidative damage rats (Nair et al, 2020). In the present study, 600 mg/kg ALA supplementation for aged breeder hens increased the level of E2 in the serum significantly.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Previous studies have noted that ALA can enhance the antioxidants enzymes like superoxide dismutase, by reducing the substrate and free radicals to promote the lipid stability in birds (Kofuji, Nakamura, Nakamura, Isobe, Murata, & Kawashima, 2008;Li et al, 2019 (Liu, Lin, Mi, Li, et al, 2018;Liu, Lin, Mi, Zeng, et al, 2018). ALA has been reported to increase the reproductive hormones in ovarian oxidative damage rats (Nair et al, 2020). In the present study, 600 mg/kg ALA supplementation for aged breeder hens increased the level of E2 in the serum significantly.…”
Section: Discussionsupporting
confidence: 59%
“…Several studies have indicated that egg‐laying rates have a positive correlation with blood oestrogen levels (Liu, Lin, Mi, Li, et al, 2018; Liu, Lin, Mi, Zeng, et al, 2018). ALA has been reported to increase the reproductive hormones in ovarian oxidative damage rats (Nair et al., 2020). In the present study, 600 mg/kg ALA supplementation for aged breeder hens increased the level of E2 in the serum significantly.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, ALA can reduce the level of ROS [51], thereby reducing the rate of apoptosis and allowing oocyte maturation, growth, and development into the large follicles. ALA can be converted into EPA and DHA, which are the precursors of 3-series prostaglandin and therefore have anti-inflammatory effects [6,52]. This mechanism could explain how ALA increases the number of large follicles.…”
Section: Discussionmentioning
confidence: 99%
“…11 Nair et al showed that cyclophosphamide-induced damage in the ovarian tissue was caused by a decrease in the endogenous antioxidant glutathione (GSH) and an increase in proinflammatory tumor necrosis factor alpha (TNF-α). 12 In a study by Khedr, it was emphasized that cyclophosphamide-induced infertility was associated with an increase in malondialdehyde (MDA) -a lipid peroxidation (LPO) product in the ovarian tissue. 13 The information obtained from the literature suggests that antioxidant and anti-inflammatory drugs can be beneficial in the prevention or treatment of cyclophosphamide-induced infertility.…”
Section: Introductionmentioning
confidence: 99%